2010
DOI: 10.1016/j.scr.2010.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Progressive maturation in contracting cardiomyocytes derived from human embryonic stem cells: Qualitative effects on electrophysiological responses to drugs

Abstract: The field of drug testing currently needs a new integrated assay system, as accurate as systems using native tissues, that will allow us to predict arrhythmia risks of candidate drugs and the relationship between genetic mutations and acquired electrophysiological phenotypes. This could be accomplished by combining the microelectrode array (MEA) system with cardiomyocytes (CMs) derived from human embryonic stem cells (hESC) and induced pluripotential stem cells. CMs have been successfully induced from both typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 53 publications
7
109
1
Order By: Relevance
“…However, the cardiac lineages generated using this approach are relatively immature, i.e., fetal stage. While fetal stage cells may be well suited to study developmental cardiac disorders [10], maturation protocols that generate more functionally mature lineages may be more useful to study late-onset disease phenotypes and accurately evaluate drug responses [11][12][13][14]. Our study further suggests that the technology can be expanded to study not just genetic influences, particularly in the rapidly emerging era of genome editing [15], but also environmental teratogens (toxins, chemicals, drugs, infections) to define the mechanisms by which they impact fetal cardiac development or differentiation.…”
Section: Future Directions and Clinical Applicationsmentioning
confidence: 99%
“…However, the cardiac lineages generated using this approach are relatively immature, i.e., fetal stage. While fetal stage cells may be well suited to study developmental cardiac disorders [10], maturation protocols that generate more functionally mature lineages may be more useful to study late-onset disease phenotypes and accurately evaluate drug responses [11][12][13][14]. Our study further suggests that the technology can be expanded to study not just genetic influences, particularly in the rapidly emerging era of genome editing [15], but also environmental teratogens (toxins, chemicals, drugs, infections) to define the mechanisms by which they impact fetal cardiac development or differentiation.…”
Section: Future Directions and Clinical Applicationsmentioning
confidence: 99%
“…While the ability to assess the effect of a compound on a single ion channel (K + , Na + , Ca 2+ ) or complex channel network (AP, FPD) enhances the prediction value of hPSC-cardiomyocytes, the absence of species variation renders these cells an impeccable humanised in vitro test system. A number of studies have demonstrated the potential application of hPSCcardiomyocytes in evaluating pharmacological safety 23,[32][33][34][35][36] . For example, while E-4031 (I Kr blocker) and Satalol (class III anti-arrhythmic agent; I Ks blocker) were reported to induce QT prolongation, administration of quinidine (class I anti-arrhythmic agent; I Na blocker) and TTX (Na + channel blocker) resulted in a dose-dependent reduction in conduction velocity 18,32 .…”
Section: Human Pluripotent Stem Cells and Drug Discovery: A New Beginmentioning
confidence: 99%
“…Alternatively, hPSC-derived cardiomyocytes at the current maturity could be studied and the cardiac channels deconstructed such that a mature phenotype could be generated via computer-based modeling (31). A less optimal approach to maturity is to culture for extended periods of time, as 1 year in culture led to myosin and band changes indicative of adult cardiomyocytes (32,33). Thus, there are a multitude of avenues to explore maturing cardiomyocytes should the scientific need arise.…”
Section: Cardiomyocytesmentioning
confidence: 99%